Pengembangan Modul Pembelajaran Dasar Listrik dan Elektronika Berbasis PHET Simulation untuk Siswa Kelas X Teknik Instalasi Tenaga Listrik SMK - Aditya Dwi Raja Kamansastra; Bagus Dwi Cahyono; Siswo Wardoyo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aimed to develop a PhET Simulation-based learning module for Basic Electrical and Electronics and to evaluate its feasibility and implementation in supporting the learning process of tenth-grade students in the Electrical Power Installation Engineering program at SMKN 4 Kota Tangerang. The study was motivated by teacher-centered learning practices and the limited use of instructional media, which relied primarily on Microsoft PowerPoint, resulting in low student participation and learning outcomes below the Minimum Mastery Criteria (MMC) on electrical circuit topics. This research employed the Research and Development (R&D) method using the Lee and Owens development model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included media experts, material experts, and 34 tenth-grade students. Data were collected through observations, interviews, questionnaires, and assessments of cognitive, affective, and psychomotor learning outcomes. During the implementation stage, students used the module integrated with PhET Simulation to design and test electrical circuits virtually. The findings indicated that the developed module achieved an excellent category based on expert validation and received positive responses from students. The module also enhanced students' participation, engagement, and understanding of electrical circuit concepts through interactive, contextual, and practice-oriented learning experiences. Therefore, the PhET Simulation-based learning module is feasible and effective as an instructional medium for Basic Electrical and Electronics learning in vocational high schools.